Passing in the soccer World Cup 2002 - Scoulding, A.; James, N.; Taylor, J. (International Journal of Performance Analysis in Sport, 2004)
The differences in playing patterns of soccer teams has been, and remains to be, one of the largest areas of post-match performance analysis within association football. Many studies try to encapsulate the multiple facets of play and consequently only provide limited detail in any one area (Low et al., 2002; Hughes Robertson and Nicholson, 1988). This study aimed to provide a more detailed insight into passing during the 2002 World Cup whereby post event analysis of six group matches was undertaken (3 each for a successful and an unsuccessful team, based on qualification through the group stages, Stanhope, 2001). The resulting passes (>4000) were analysed for start and finish positions (for length of pass), whether they were played to a player or space, played first time or after a dribble and some outcome was recorded e.g.possession lost or retained. The coding process was designed and recorded using a computerised notational analysis software package, the Noldus Observer Video-Pro (Noldus Information Technology, 2001). The data was then transferred to SPSS v11.01 (SPSS Inc.) for statistical analysis (Chi Square). Reliability measures were conducted at the level of the subsequent analysis, as suggested by Hughes, Cooper and Nevill (2002). In this respect all defined performance measures provided good reliability estimates (<5% error) with a further assessment of the time coding process (built into the Observer) measuring the time from when the player received the ball to when the pass was made. This resulted in a low average error of 0.08 seconds but a relatively large spread (± 1.08 s). The passing strategy for the successful and unsuccessful teams did not differ (types of pass employed) suggesting that this performance indicator does not easily discriminate teams at this level. The only apparent difference existed in the pre-defensive area of the field (near the halfway line, James, Mellalieu & Holley, 2002) where the unsuccessful team tended to play significantly more passes. This observed difference was thought suggestive of a difference in total possession in this area rather than indicative of a strategy difference. The findings thus suggested that there was no difference in passing ability between the two teams within this study even though they differed markedly in terms of success in the tournament. Consequently it is suggested that either the criteria used were not sensitive enough to detect differences in passing or the teams were of a similar standard and other factors determined match outcomes.